PENGARUH MEDIA PEMBELAJARAN MATEMATIKA MATERI PENGUKURAN BERBASIS WEBSITE MENGGUNAKAN GOOGLE SITES PADA HASIL BELAJAR SISWA KELAS V SD - Rahmawati; Intan Dwi Hastut; Abdillah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of website-based mathematics learning media using Google Sites on the learning outcomes of fifth-grade elementary school students. The background of this study is based on students’ low learning outcomes in measurement material and the dominance of conventional teaching methods that limit student engagement. This research employed a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The research subjects consisted of 52 fifth-grade students at SDN 02 Dompu, divided into an experimental class (27 students) and a control class (25 students). Data were collected through tests, observation, and documentation. Data analysis included validity and reliability tests, normality tests, homogeneity tests, and hypothesis testing using a t-test. The results showed that the average posttest score of the experimental class was higher than that of the control class. The t-test results indicated a significance value of < 0.05, meaning the alternative hypothesis was accepted. Therefore, it can be concluded that website-based learning media using Google Sites has a significant effect on improving students’ learning outcomes in measurement material.